The Effects of Viral Load Burden on Pregnancy Loss among HIV-Infected Women in the United States. (25th October 2015) - Cates, Jordan E.; Westreich, Daniel; Edmonds, Andrew; Wright, Rodney L.; Minkoff, Howard; Colie, Christine; Greenblatt, Ruth M.; Cejtin, Helen E.; Karim, Roksana; Haddad, Lisa B.; Kempf, Mirjam-Colette; Golub, Elizabeth T.; et al.
Abstract : Background . To evaluate the effects of HIV viral load, measured cross-sectionally and cumulatively, on the risk of miscarriage or stillbirth (pregnancy loss) among HIV-infected women enrolled in the Women's Interagency HIV Study between 1994 and 2013. Methods . We assessed three exposures: most recent viral load measure before the pregnancy ended, log10 copy-years viremia from initiation of antiretroviral therapy (ART) to conception, and log10 copy-years viremia in the two years before conception. Results . The risk of pregnancy loss for those with log10 viral load >4.00 before pregnancy ended was 1.59 (95% confidence interval (CI): 0.99, 2.56) times as high as the risk for women whose log10 viral load was ≤1.60. There was not a meaningful impact of log10 copy-years viremia since ART or log10 copy-years viremia in the two years before conception on pregnancy loss (adjusted risk ratios (aRRs): 0.80 (95% CI: 0.69, 0.92) and 1.00 (95% CI: 0.90, 1.11), resp.). Conclusions . Cumulative viral load burden does not appear to be an informative measure for pregnancy loss risk, but the extent of HIV replication during pregnancy, as represented by plasma HIV RNA viral load, predicted loss versus live birth in this ethnically diverse cohort of HIV-infected US women.